Peningkatan Keterampilan Menulis Teks Eksplanasi Menggunakan Model RADEC Berbantuan Media Audiovisual pada Peserta Didik Kelas V SDN 24 Ujung Gurun - Afriani, Iim; Suriani, Ari; Desyandri, Desyandri; Sukma, Elfia (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the improvement of writing skills for explanatory texts through the application of the RADEC model assisted by audiovisual media for fifth-grade students at SDN 24 Ujung Gurun. This research is a Classroom Action Research (CAR) with both qualitative and quantitative approaches, carried out in two cycles, each consisting of stages of planning, implementation, observation, and reflection. The subjects of the study include the classroom teacher and 28 fifth-grade students. Data collection techniques using observation, writing skill tests, and documentation. Quantitative data is analyzed by calculating the percentage of indicator achievement, while qualitative data is analyzed through the process of data reduction, presentation, and drawing conclusions. The research results show a significant increase in all observed aspects. The quality of the teaching module improved from 87.5% (good) in cycle I to 97.22% (very good) in cycle II. The implementation of learning by the teacher increased from 82.14% to 96.42%, while student activity also rose from 80.35% to 96.42%. The results of students' explanatory text writing skills improved from 68.91% (poor) in cycle I to 84.49% (good) in cycle II. Thus, the RADEC model assisted by audiovisual media proved effective in improving explanatory text writing skills among fifth-grade students of SDN 24 Ujung Gurun.